Spinal osteochondroma: A rare cause of spinal compression – A case report and review of literature - chouhan, Aditya; Kumar, Naveen; Aravind, Muttu; Johri, Taarini; Dalvie, Samir (Indian Journal of Case Reports, 2026)
Osteochondroma is a common benign bone tumor, but spinal involvement is rare. They are rare in the spine, with frequencies ranging from 3% for solitary forms to 7–9% for multiple forms. We report a rare case of spinal osteochondroma in an 18-year-old male presenting with difficulty in walking. Imaging revealed well-defined growth with cortical and medullary continuity with parent bone, arising from the right-sided pedicle of T1, encroaching adjacent vertebrae, compressing the spinal canal, suggesting osteochondroma. The patient underwent extraperiosteal excision using an ultrasonic scalpel. Although rare, spinal osteochondroma should be considered in the differential diagnosis of myelopathy. Timely surgical intervention can lead to excellent outcomes.